968 Impact of individual motivation differences on reducing sedentary behaviour. (24th April 2018) - Hermans, V; Van Naemen, L; Seghers, J; Godderis, L; Daenen, L
Abstract : Introduction: Reviews small effects for interventions sitting behaviour. This study aimed at evaluating basic psychological needs (need for competence, for autonomy and for relatedness) reduction in sitting behaviour. Methods: This study is part of the Move@TheOffice RCT-study in the offices a large pharmaceutical company. The experimental group (19 participants) received a multiintervention to reduce sitting. To measure the basic psychological needs, the Work-related Basic eed atisfaction cale was used. The BREQ-3 measured the degree of motivation regulation to reduce sitting. Sitting was measured using the micro ActivPal TM monitor. Data were analysed using SPSS. Results: Significant decrease (p<0, 05) in sitting time was found the experimental group. A significant BREQ-index was found after the intervention (p<0.05), a higher to decrease sitting behaviour. This was related to the basic psychological needs, mainly due to a higher of the need for autonomy (p<0.01). Conclusion: Need for autonomy important in the motivation to reduce sitting. Presenting different to reduce sitting seems to autonomy. Future studies are warranted to evaluate if more emphasis on the need relatedness by organising e.g. group discussions during the interventions, results in a larger reduction sitting behaviour.